Association between maternal health service utilization and under-five mortality rate in China and its provinces, 1990-2017 - Jingya Zhang; Haoran Li; Bincai Wei; Rongxin He; Bin Zhu; Ning Zhang; Ying Mao (BMC, 2024)
Abstract Background The United Nations (UN) Sustainable Development Goal − 3.2 aims to eliminate all preventable under-five mortality rate (U5MR). In China, government have made efforts to provide maternal health services and reduce U5MR. Hence, we aimed to explore maternal health service utilization in relation to U5MR in China and its provinces in 1990-2017. Methods We obtained data from Global Burden of Disease 2017, China Health Statistics Yearbook, China Statistical Yearbook, and Human Development Report China Special Edition. The trend of U5MR in each province of China from 1990 to 2017 was analyzed using Joinpoint Regression model. We measured the inequities in maternal health services using HEAT Plus, a health inequity measurement tool developed by the UN. The generalized estimating equation model was used to explore the association between maternal health service utilization (including prenatal screening, hospital delivery and postpartum visits) and U5MR. Results First, in China, the U5MR per 1000 live births decreased from 50 in 1990 to 12 in 2017 and the average annual percentage change (AAPC) was − 5.2 (p < 0.05). Secondly, China had a high maternal health service utilization in 2017, with 96.5% for prenatal visits, 99.9% for hospital delivery, and 94% for postnatal visits. Inequity in maternal health services between provinces is declining, with hospital delivery rate showing the greatest decrease (SII, 14.01 to 1.87, 2010 to 2017). Third, an increase in the rate of hospital delivery rate can significantly reduce U5MR (OR 0.991, 95%CI 0.987 to 0.995). Postpartum visits rate with a one-year lag can reduce U5MR (OR 0.993, 95%CI 0.987 to 0.999). However, prenatal screening rate did not have a significant effect on U5MR. Conclusion The decline in U5MR in China was associated with hospital delivery and postpartum visits. The design and implementation of maternal health services may provide references to other low-income and middle-income countries.